Studi Komparatif: Implementasi Pendidikan Karakter di MI Swasta Se-Kecamatan Alang-Alang Lebar Kota Palembang - Najamuddin Royes; Miftahul Husni; Ibrahim Ibrahim (JIP Jurnal Ilmiah PGMI, 2019)
Abstract: Character building is one of the goals of National Education, of course, it has become an obligation for every educational institution to become the main pioneer in habituating characters to students, as the primary education level, of course, the Islamic Elementary School gets the largest portion for the development of children's characteristics at an early age. This study entitled: Comparative Study: Implementation of Character Education in MI throughout Alang-Alang Lebar District, Palembang City. The formulation of the problem in this study is what is the implementation of character education in Private MI in the Alang-Alang Lebar District in Palembang City, what is the difference between the implementation of character education in private MI in the Alang-Alang Lebar District in Palembang. This study used a qualitative descriptive method, which is a method that aims to make a systematic or factual and accurate picture or painting of what is happening in the field. Data collection in this study was obtained through observation, interview, and documentation techniques, and the data analysis technique used data triangulation, namely data reduction, data display, and conclusions. The results of the research on the Character Education Implementation Process at Insanul Fitroh Madrasah Ibtidaiyah were implemented through 3 processes, including 1. Implementation through the process of habituation in teaching and learning, 2. Implementation through routine Madrasah activities, 3. Implementation through extracurricular activities. The process of implementing Character Education in Al-Hikmah Islamic Elementary School through 4 receptacles, including 1. Character implementation through routine activities, 2. Implementation of characters through spontaneous activities, 3. Character implementation through exemplary activities, 4. Character implementation through Subjects. And as for the Comparative Character Education Implementation between Madrasah Ibtidaiyah Insanul Fitroh and Madrasah ibtidaiyah Al-Hikmah is located in the process of character building, some of the characters implanted differ between these two madrasah in their habituation and habitual processes, each character implanted with habituation emphasis is different. Key words: Character education, MI Insanul Fitroh and MI Al-Hikmah